2015
DOI: 10.1002/chem.201502842
|View full text |Cite
|
Sign up to set email alerts
|

Glyconanomaterials for Combating Bacterial Infections

Abstract: Bacterial infections constitute an increasing problem to human health in response to build-up of resistance to present antibiotics and sluggish development of new pharmaceuticals. However, a means to address this problem is to pinpoint the drug delivery to - and into - the bacteria. This results in a high local concentration of the drug, circumventing the increasingly high doses otherwise necessary. Combined with other effectors, such as covalent attachment to carriers, rendering the drugs less degradable, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 138 publications
0
13
0
Order By: Relevance
“…‘Hijacking’ prokaryotic glycosylation systems to exploit them for glycobiotechnological applications including glycoconjugate vaccine and humanised glycoprotein production is a promising perspective for future developments (Cuccui and Wren 2015). The challenges that remain for these approaches to reach full biotechnological maturity will include new strategies for creation of new glycomaterials including glyconanomaterials, evaluation of their targeting potential and their drug delivery properties, as well as characterisation of the internalisation process of these neo -glycoconjugates (Ramström and Yan 2015). Vaccines against both Gram-negative and Gram-positive organisms have already been developed, and efficacy testing has thus far demonstrated that the vaccines are safe and that robust immune responses are being detected.…”
Section: N-linked Bacterial Glycoproteinsmentioning
confidence: 99%
“…‘Hijacking’ prokaryotic glycosylation systems to exploit them for glycobiotechnological applications including glycoconjugate vaccine and humanised glycoprotein production is a promising perspective for future developments (Cuccui and Wren 2015). The challenges that remain for these approaches to reach full biotechnological maturity will include new strategies for creation of new glycomaterials including glyconanomaterials, evaluation of their targeting potential and their drug delivery properties, as well as characterisation of the internalisation process of these neo -glycoconjugates (Ramström and Yan 2015). Vaccines against both Gram-negative and Gram-positive organisms have already been developed, and efficacy testing has thus far demonstrated that the vaccines are safe and that robust immune responses are being detected.…”
Section: N-linked Bacterial Glycoproteinsmentioning
confidence: 99%
“…Such AIE effects have more recently emerged as a general and robust strategy to sense molecular entities and physical factors (e.g., force, temperature, acidity/basicity, potential, viscosity), and monitor biological and physical processes . These attractive features of AIE‐active structures incited us to further explore the N ‐amidinated fluoroquinolones as probes in general, and in addressing the rich molecular interactions engaged in their therapeutic action in particular …”
Section: Introductionmentioning
confidence: 99%
“…[7] These attractive features of AIE-actives tructures incited us to further explore the N-amidinated fluoroquinolones as probesing eneral,and in addressing the rich molecular interactions engaged in their therapeutic action in particular. [8] As at ypical fluoroquinolone, ciprofloxacin (CIP)g enerally showsaconsiderably complex fluorescenceb ehavior.I ts emission is highly responsive to environmental factors, [9] including pH, solvent polarity, [10] and ar ange of interacting species, such as bromanil, [11] iodine, [12] amino acids/peptides, [13] and serum albumin. [14] In the solid state, ciprofloxacin generally suffers from aggregation-causedq uenching( ACQ), thus showing only faint fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…During the last years, new generations of these drug classes have emerged by chemical modification and optimization to inhibit a vast number of virulence factors, but it seems unlikely that this can go indefinitely. Therefore, enormous efforts have been made in recent years to design new and efficient scaffolds including proteins [17,18], fullerenes [19], calixarenes [20], nanomaterials [21] and polymers [22] displaying glycans in a multivalent fashion that target anti-adhesive binding events. This review highlights recent advances in the development of glycopeptide and -mimetic scaffolds to study host-pathogen interactions.…”
Section: Bacterial Infectionsmentioning
confidence: 99%